Influence of the biopreparation “Gaupsin” on storability of mandarin fruits - Mikeladze, Zurab; Kutaladze, Nunu; Lominadze, Shota (International Journal of Scientific Research and Management (IJSRM), 2021)
Our goal is to incorporate in the complex of citrus agrotechnical activities such technologies that will significantly increase the natural storability of mandarin fruits, in production and in short time in normal conditions, in the process of storage and sale. To this end, we conducted a large-scale experiment and included in the complex of agrotechnical measures the biopreparation “Gaupsin” of Ukrainian production, which protects plants from pests and diseases, promotes their growth and development, improves fruit bearing and qualitative indicators, in their number, increasing of storability. Gaupsin, as a bacterial fungicidal preparation, exhibits insecticidal properties, destroys pests, and with these and other properties, Gaupsin allows us to obtain high-quality and storable mandarin fruits. Its use is effective for  processing of containers and boxes. At the same time, the preparation is environmentally friendly. Use of the biopreparation Gaupsin has shown a tendency to improve agrochemical parameters of soil; yield and quality parameters significantly increase. The parameters of adverse action of pests and diseases (especially silver mites and anthracnose) decreased to minimum. Natural fruit storability increases, at the cost of improvement of general physiological condition of fruits and neutralization of the pathogen, which shows the positive impact of the biopreparation in terms of fruit bearing. It should also be noted that the use of Gaupsin has practically eliminated the alternating bearing of mandarins and we every year obtain quantitatively and qualitatively stable harvest.During the experimental period, we monitored the spread of pest disease on a monthly basis by means of commissions, focusing on monitoring the spread of such pests that significantly harm the growth and crop quality of mandarin. These include silver mites (40-45% harmfulness), citrus red mites Panonychus citri (45-50% harmfulness), elongated grey citrus scale (20-25% harmfulness), anthracnose (20%), wart disease (25%), black spots  (25-30%). They each damage leaves, fruits, twigs and buds of plants. Anthracnose is particularly potent in conditions of fruit storage. The blackness caused by the fungal excretion of saprophyte fungi inhibits plant respiration and photosynthesis processes. The crop decreases and fruit loses its commodity, so these fruits are most easily damaged during storage by fungi of penicillium group and they spoil as quickly as possible. Losses from fruit breakdown are so significant that such fruits are virtually unusable not only for fresh consumption, but also from the point of view of industrial processing. At the same time, the environment is heavily polluted and it is also dangerous in subsequent years.          Based on our experimental data, we have developed calibrator for mandarin fruit and a mobile device for processing with Gaupsin, which has been handed over to newly established cooperatives. Serial manufacturing of such simple machine will resolve the problem of commodity processing of mandarin fruit by the biopreparation Gaupsin, and the farmer will be able to obtain on the spot products storable in commodity state, and the retailer will be guaranteed to minimize losses  during the transportation and sale.